Current state of safety climate among food delivery service in Kuantan - Nurliyana, Moh Hussin; Nur Wahida Athi’roh, Mohd Yusoff (Penerbit Universiti Malaysia Pahang, 2024)
The gig economy has developed as a transformational force in modern labor markets, typified by short-term, freelancer, or independent employment arrangements. It includes a wide range of on-demand labor where individuals work as independent contractors, offering services or performing tasks via digital platforms or applications. The expansion of this industry has provided workers with unprecedented freedom and opportunity, but it has also presented new concerns, notably in terms of occupational safety. The most popular gig works prior Covid-19 pandemic include food delivery riders. This study aims to investigate the safety climate among food delivery services in Kuantan. This current study was focusing on the safety views of Grab’s delivery service workers in Kuantan. About 100 respondents participated in this study through convenience sampling. The safety climate assessment was conducted using the NORDIC safety climate questionnaire. From the result, the highest mean value of the seven safety domains was in the Safety procedures and rules domain (2.78), and the lowest mean value belonged to the safety climate domain (2.41).